Changes and factors of thermal discharge from 2013 to 2023: A case study of the Tianwan nuclear power plant - Xiangle Jiang; Wenjin Zhu; Yang Zhang; Qing Xu; Xiaotian Dong (Ecological Indicators)
Monitoring seawater temperature changes near nuclear power plants is vital for safe operation and ecological balance. We developed a sea surface temperature (SST) retrieval model incorporating water vapor content to analyze thermal discharge from China’s Tianwan Nuclear Power Plant. Through remote sensing and numerical simulation techniques, we analyzed changes and factors of thermal discharge from a unique perspective of three-dimensional, tidal, and planktonic microorganisms. Results showed: (1) The SST retrieval algorithm we modified had high accuracy and applicability; (2) Between 2013 and 2023, the increase in nuclear units had intensified thermal discharge, expanding the affected marine areas; (3) The thermal discharge in spring and summer had a more pronounced impact on the temperature rise areas; (4) Tidal dynamics and seasonal variations, especially spring tides, significantly influenced thermal discharge and mixing; (5) Tidal currents improved vertical mixing, with spring tides weakening stratification and raising bottom temperatures; (6) Planktonic microorganism diversity peaked in spring, autumn, and winter, while summer discharge reduced abundance. The study provided valuable insights into managing the environmental impacts of nuclear power plants. Further, it strengthened the understanding of the ecological consequences of thermal discharges.